Linguistic poetic features of a portrait in prose by L. Ulitskaya (a case study of the novel «Medea and Неr Chidren») - Гамали, Ольга Игоревна; Каневская, Ольга Борисовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article analyzes the linguistic and poetic features of portraits in the novel «Medea and Her Children» by L. Ulitskaya, one of the most famous authors of the contemporary Russian literature. The range of portrait descriptions varies from the detailed description of the character to the indication of only one characteristic feature. Especially stands out self-portrayal in the speech of the characters as a projection of their inner and outer being. The portrait can be not only static, but also dynamic (facial expressions, gestures, postures, movements). Philological analysis of descriptions of the characters’ appearance contributes to the disclosure of their images and the design of works in general. Was identified the main types of portrait descriptions (expositions, perceptions, situations), leitmotifs and the most frequent signs of the characters’ appearance (hair, eyes, «national type»), tropes and their varieties (color, emotional, estimated epithets, «intellectual» and «household» comparisons, lexical repetitions), used for creating portraits of characters. Was emphasized a compound of the external and psychological characteristics in the portraits, a complex combination of the humor, irony and high tragedy, inherent to the Ulitskaya’s prose.